Clinical outcome after laparoscopic Nissen fundoplication in patients with GERD and PPI refractory heartburn. Issue 4 (15th January 2020) - Schwameis, Katrin; Oh, Daniel; Green, Kyle M; Lin, Brenda; Zehetner, Jörg; Lipham, John C; Hagen, Jeffrey A; DeMeester, Steven R
Summary: Typical reflux symptoms that respond well to proton pump inhibitor (PPI) therapy are key factors predictive of an excellent outcome with antireflux surgery for gastroesophageal reflux disease (GERD). Our aim was to evaluate whether poor preoperative heartburn (HB) relief with PPIs was associated with a worse outcome after Nissen fundoplication. Patients with a main symptom of HB and a positive pH-test who had a laparoscopic Nissen fundoplication between January 2008 and December 2014 were included. Prior to surgery, patients graded how effectively their HB symptoms were relieved by PPIs. Three groups were defined: good response (76–100% relief), partial response (26–75% relief) and poor response (0–25% relief). Outcomes and satisfaction were assessed at a minimum of 1 year after fundoplication. There were 129 patients who met inclusion criteria and 75 agreed to participate. The median follow-up was 48 months. Prior to Nissen fundoplication 13 patients had a good HB response to PPI-therapy, 36 had a partial response and 26 had a poor response. All patients were satisfied with their HB relief after fundoplication (mean satisfaction score: 9.5/10) and there was no difference in satisfaction score or heartburn relief between groups. Heartburn symptoms that respond poorly to PPI therapy are reliably relieved with a Nissen fundoplication in patients with objectively confirmed GERD. Patient satisfaction after Nissen fundoplication was excellent and was similar in patients with poor versus excellent HB relief with preoperative PPI therapy. Therefore, antireflux surgery is an option for patients with HB and confirmed GERD regardless of the degree of relief of HB symptoms provided by PPI medications.